Association of left ventricular ejection fraction with worsening renal function in patients with acute heart failure: insights from the RELAX‐AHF‐2 study. (9th October 2020) - Feng, Siting; Janwanishstaporn, Satit; Teerlink, John R.; Metra, Marco; Cotter, Gad; Davison, Beth; Felker, G. Michael; Filippatos, Gerasimos; Pang, Peter; Ponikowski, Piotr; Sama, Iziah E.; Voors, Adriaan A.; et al.
Abstract : Aims: Whether risk of worsening renal function (WRF) during acute heart failure (AHF) hospitalization or the association between in‐hospital WRF and post‐discharge outcomes vary according to left ventricular ejection fraction (LVEF) is uncertain. We assessed incidence of WRF, factors related to its development and impact of WRF on post‐discharge outcomes across the spectrum of LVEF in patients enrolled in RELAX‐AHF‐2. Methods and results: A total of 6112 patients who had LVEF measured on admission and renal function determined prospectively during hospitalization were included. WRF, defined as a rise in serum creatinine ≥0.3 mg/dL from baseline through day 5, occurred in 1722 patients (28.2%). Incidence increased progressively from lowest to highest LVEF quartile ( P  < 0.001). After baseline adjustment, WRF risk in Q4 (LVEF >50%) remained significantly greater than in Q1 (LVEF ≤29%; hazard ratio 1.2, 95% confidence interval 1–1.43; P  = 0.050). Age and comorbidity burden including chronic kidney disease increased as LVEF increased. Neither admission haemodynamic abnormalities, extent of diuresis during hospitalization nor residual congestion explained the increased incidence of WRF in patients with higher LVEF. Serelaxin treatment and diuretic responsiveness were associated with reduced risk of WRF in all LVEF quartiles. WRF in patients in the upper three LVEF quartiles increased risk of post‐discharge events. Conclusions: Worsening renal function incidence during AHF hospitalization increases progressively with LVEF. Greater susceptibility of patients with higher LVEF to WRF appears more related to their advanced age and worse underlying kidney function rather than haemodynamic or treatment effects. WRF is associated with increased risk of post‐discharge events except in patients in the lowest LVEF quartile.